2007
DOI: 10.1093/nar/gkm082
|View full text |Cite
|
Sign up to set email alerts
|

C1D and hMtr4p associate with the human exosome subunit PM/Scl-100 and are involved in pre-rRNA processing

Abstract: The exosome is a complex of 3′–5′ exoribonucleases and RNA-binding proteins, which is involved in processing or degradation of different classes of RNA. Previously, the characterization of purified exosome complexes from yeast and human cells suggested that C1D and KIAA0052/hMtr4p are associated with the exosome and thus might regulate its functional activities. Subcellular localization experiments demonstrated that C1D and KIAA0052/hMtr4p co-localize with exosome subunit PM/Scl-100 in the nucleoli of HEp-2 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
157
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(170 citation statements)
references
References 39 publications
12
157
0
1
Order By: Relevance
“…4A). This suggests that a stable Mpp6-Rrp6-Rrp47 complex can assemble as previously shown in vitro using human proteins (34). Importantly, the region (MC-2) within Mpp6 that binds to the Nrd1 CID turns out to mediate the interaction with Rrp6 as well (Fig.…”
Section: Characterization Of the Nrd1 Cid-mpp6supporting
confidence: 77%
See 2 more Smart Citations
“…4A). This suggests that a stable Mpp6-Rrp6-Rrp47 complex can assemble as previously shown in vitro using human proteins (34). Importantly, the region (MC-2) within Mpp6 that binds to the Nrd1 CID turns out to mediate the interaction with Rrp6 as well (Fig.…”
Section: Characterization Of the Nrd1 Cid-mpp6supporting
confidence: 77%
“…Mpp6 Interacts with Rrp6 -Human Mpp6 interacts directly with PM-Scl100 (human Rrp6) by Y2H and co-IP experiments (33,34). We consistently found that yeast Mpp6 also interacts with Rrp6 by Y2H assay (Fig.…”
Section: Characterization Of the Nrd1 Cid-mpp6supporting
confidence: 57%
See 1 more Smart Citation
“…11,14,64,65 Research on Rrp47 has focussed on its physical association with the exosome nuclease complex. …”
Section: The Exosome Cofactor Rrp47mentioning
confidence: 99%
“…SKIV2L2 is also associated with the human exosome subunit PM/ Scl-100 and is involved in pre-rRNA processing [36]. Medaka SKIV2L2 encodes a protein of 1036 amino acid residues, whereas the hjc mutation presumably produces a mutant protein containing 366 amino acid residues of SKIV2L2 N-terminus and four amino acid residues derived from the intron.…”
Section: Discussionmentioning
confidence: 99%